IMPLEMENTATION OF OFFICIAL VEHICLE ASSET MANAGEMENT POLICY AT THE TRADE, INDUSTRY, ENERGY AND MINERAL RESOURCES OFFICE IN SINJAI REGENCY - Nurkumalasari Syam; Pirda Pirda; Mariati Rahman (Universitas Negeri Makassar, 2026)
This study aims to determine the implementation of vehicle asset management policies at the Department of Trade, Industry, Energy and Mineral Resources of Sinjai Regency and the obstacles faced. The results of the study indicate that the implementation of vehicle asset management policies at the Department of Trade, Industry, Energy and Mineral Resources of Sinjai Regency found that: 1) Communication between Fields and UPTD is fairly good. There is an effective internal communication system to provide the latest information on vehicle condition reports and STNK renewal schedules and maintain effective communication by involving all relevant parties in the vehicle management process through the official WA group. 2) The resources from the available official vehicle facilities are sufficient. However, the budget allocation is not adequate for vehicle maintenance. It is important to continue to monitor and manage resources efficiently. Periodic evaluation of budget availability to support better vehicle maintenance. 3) The disposition of operational official vehicles has been well regulated. The attitude of vehicle users/holders has maintained and maintained the vehicles they own. 4) The bureaucratic structure is already in place because the asset manager is signed by the Sinjai Regent and the names of official vehicle holders are signed and coordination is carried out with the head of the service and asset manager, BKAD in reporting and accountability for regional assets. The obstacle faced is that the maintenance costs that were previously available for each unit in the last 4 years have been eliminated due to limited regional budgets since Covid-19 and the local government can only afford to pay STNK renewal taxes.